The island - Hislop, Victoria, 1959- (Headline, 2005)
On the brink of a life-changing decision, Alexis Fielding longs to find out about her mother's past. But Sofia has never spoken of it. All she admits to is growing up in a small Cretan village before moving to London. When Alexis decides to visit Crete, however, Sofia gives her daughter a letter to take to an old friend, and promises that through her she will learn more.